2017
DOI: 10.1136/archdischild-2016-312278
|View full text |Cite
|
Sign up to set email alerts
|

Parental experience of interaction with healthcare professionals during their infant’s stay in the neonatal intensive care unit

Abstract: Factors including the context of infant admission, interprofessional consistency, humane touches of staff and the transition into the culture of the neonatal unit are important issues for parents. These issues warrant further investigation to facilitate individualised family needs, attachment between parents and their baby and the professional team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 22 publications
4
69
0
Order By: Relevance
“…On a more positive note, parents were also sensitive to small gestures of caring from the part of staff. Similar findings as to the importance to parents of signs of kindness and respect from NICU staff have emerged in previous studies [18, 26].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…On a more positive note, parents were also sensitive to small gestures of caring from the part of staff. Similar findings as to the importance to parents of signs of kindness and respect from NICU staff have emerged in previous studies [18, 26].…”
Section: Discussionsupporting
confidence: 89%
“…The parents interviewed in the present study felt it was vital for them to be able to trust in the smooth functioning of the NICU and for staff to communicate with them in a comprehensible, thorough and empathic way . Previous studies of NICU parents have identified similar needs [1618, 26]. Organizational factors making it harder for staff to meet these needs merit special consideration.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have also shown the importance of a primary nurse. 19,23 In addition to a primary nurse, some parents experienced a variable level of individualized support in the unit. This was evident in the units where the whole staff had not finished the training and indicates that without full adoption of the intervention the practices remain inconsistent.…”
Section: Discussionmentioning
confidence: 99%